Analisis Profil Literasi Sains Siswa Kelas VIII di Sidoarjo Berdasarkan Indikator PISA 2015 - Pratiwi, Zuliana Eka; Hidayati, Siti Nurul; Aulia, Ernita Vika (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – This research aims to describe the initial scientific literacy skills of students at SMP Sidoarjo. The researcher also reviewed each indicator used to measure scientific literacy skills to provide educators with ideas on how to improve these skills in the future.Method – This type of research is a survey design. The data analysis technique used is quantitative descriptive. The science literacy ability test designed consists of nine questions adopted from the PISA 2015 science literacy test questions with three indicators. The indicators used are indicators of aspects of science literacy competency. Researchers also examine each indicator used to measure science literacy skills.Findings – The results of the study showed that students' scientific literacy skills were generally good. However, there were deficiencies in the indicators of evaluating and designing scientific investigations which were considered low. This was due to the low knowledge of content, procedures, and epistemics of students resulting in a lack of students' ability to design and evaluate scientific investigations. In addition, internal and external factors also contributed to this low ability. The solution that can be done is to use learning methods that develop high-level skills and are student-centered. Research Implications – This research can be useful for educators to know the profile of students' scientific literacy. Because this study has not been conducted empirically, additional research is needed to find useful methods to improve scientific literacy skills. These strategies can include appropriate learning methods to improve overall scientific literacy skills.